Investigation of Human Exposure to Triclocarban after Showering and Preliminary Evaluation of Its Biological Effects - Schebb, Nils Helge; Inceoglu, Bora; Ahn, Ki Chang; Morisseau, Christophe; Gee, Shirley J; Hammock, Bruce D (Environmental science & technology, 2011)
The antibacterial soap additive triclocarban (TCC) is widely used in personal care products. TCC has a high environmental persistence. We developed and validated a sensitive online solid-phase extraction−LC−MS/MS method to rapidly analyze TCC and its major metabolites in urine and other biological samples to assess human exposure. We measured human urine concentrations 0−72 h after showering with a commercial bar soap containing 0.6% TCC. The major route of renal elimination was excretion as N-glucuronides. The absorption was estimated at 0.6% of the 70 ± 15 mg of TCC in the soap used. The TCC-N-glucuronide urine concentration varied widely among the subjects, and continuous daily use of the soap led to steady state levels of excretion. In order to assess potential biological effects arising from this exposure, we screened TCC for the inhibition of human enzymes in vitro. We demonstrate that TCC is a potent inhibitor of the enzyme soluble epoxide hydrolase (sEH), whereas TCC’s major metabolites lack strong inhibitory activity. Topical administration of TCC at similar levels to rats in a preliminary in vivo study, however, failed to alter plasma biomarkers of sEH activity. Overall the analytical strategy described here revealed that use of TCC soap causes exposure levels that warrant further evaluation.